The Gut of Healthy Infants in the Community as a Reservoir of ESBL and Carbapenemase-Producing Bacteria - Ali F. Saleem; Ahreen Allana; Lauren Hale; Alondra Diaz; Raul Salinas; Cristina Salinas; Shahida M. Qureshi; Aneeta Hotwani; Najeeb Rahman; Asia Khan; Anita K. Zaidi; Patrick C. Seed; et al. (MDPI AG, 2020)
The recent rapid rise of multi-drug resistant Enterobacteriaceae (MDR-E) is threatening the treatment of common infectious diseases. Infections with such strains lead to increased mortality and morbidity. Using a cross-sectional study, we aimed to estimate the prevalence of gut colonization with extended spectrum beta-lactamase (ESBL) producing Enterobacteriaceae among healthy infants born in Pakistan, a setting with high incidence of MDR-E infections. Stool samples were collected from 104 healthy infants between the ages of 5 and 7 months. Enterobacteriaceae isolates were screened for resistance against several antimicrobial classes. Presence of ESBL and carbapenemase genes was determined using multiplex PCR. Sequence types were assigned to individual strains by multi-locus sequence typing. Phylogenetic analysis of Escherichia coli was done using the triplex PCR method. Forty-three percent of the infants were positive for ESBL-producing Enterobacteriaceae, the majority of which were E. coli. We identified several different ESBL E. coli sequence types most of which belonged to the phylogenetic group B2 (23%) or D (73%). The widespread colonization of infants in a developing country with ESBL-producing Enterobacteriaceae is concerning. The multiple sequence types and reported non-human sources support that multiple non-epidemic MDR lineages are circulating in Pakistan with healthy infants as a common reservoir.